ADCE (Art Directors Club of Europe) - (:unkn) unknown (My University, 2026)
The Art Directors Club of Europe – ADCE – is a non-for-profit organisation created in 1990 by a group of professional design and advertising associations from across Europe. Owned and managed by its members, ADCE stands for the value of Europe’s cultural diversity, simultaneously favouring and benefiting European national clubs. Internationally recognised as an authoritative voice, ADCE represents the best of local European advertising and design in an increasingly globalised market.